Implementation of the linear homogeneous recurrence relation e-classrom using the integration of VLE selfedu format and pedagogical cable approach - Batingana, Philip R. (2010)
This study aimed to generally create a linear homogenous recurrence relation (LHRR) e-learning system that adopts the adaptive and intelligent Virtual Learning Environment patterned in the selfedu format, as well as the concept of Cognitive Apprenticeship Based Learning Environment (CABLE) approach. CABLE is a combination of variety of contemporary best practices which makes use of cognitive apprenticeship, collaborative learning, metacognition, and technologies via the use of tele-apprenticeship and online or computer-mediated communication (CMC). The system takes root from five important modules: the topic delineation module, which is responsible for delineating topic and subtopic sub-modules relevant for educating LHRR to the students enrolled in the system; examination module, tasked to facilitate CABLE?s principle of scaffolding education by assigning assessment exams, designed and departmentalized by teachers, to students for them to be evaluated if they are prepared enough to take more advanced LHRR topics, messaging module, where CMC and collaborative learning are enforced as media that will aid students and teachers in having helpful academic discussions across the system; modification mechanism module, which is designed to help teachers improve the educational resources of the system by employing objective polling to gauge the approval or disapproval of the teaching body for a particular development, based on the virtue of collaborative teaching; and for homework delegation module , designed to infuse cognitive apprenticeship to aid a student?s progress for a given LHRR topic by assigning them supplementary homework online. The application only accommodates three types of educational resources text, PDF, and HTML. The HTML resources are limited to pure HTML files, having no external references to other objects (e.g. image files, script files). The application is deemed very useful for more effective and systematic delegation of LHRR educational modules recognized to be helpful for students, as well as for improving teaching efficiency among teachers by ascribing two popular pedagogical patterns highlighted in this study